2019
DOI: 10.1002/1873-3468.13378
|View full text |Cite
|
Sign up to set email alerts
|

N‐degron specificity of chloroplast ClpS1 in plants

Abstract: The prokaryotic N‐degron pathway depends on the Clp chaperone‐protease system and the ClpS adaptor for recognition of N‐degron bearing substrates. Plant chloroplasts contain a diversified Clp protease, including the ClpS homolog ClpS1. Several candidate ClpS1 substrates have been identified, but the N‐degron specificity is unclear. Here, we employed in vitro ClpS1 affinity assays using eight N‐degron green fluorescence protein reporters containing either F, Y, L, W, I, or R in the N‐terminal position. This dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 44 publications
1
14
1
Order By: Relevance
“…To understand the substrate specificity of AtClpS1, 60,61 a high‐resolution structure of AtClpS in the presence of bound peptide was needed. Initially, we tried to determine AtClpS1 in complex with an N‐degron using the LC3B fusion technique by attaching the Leu residue at the N‐terminal region of AtClpS1 for easier crystallization 62 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To understand the substrate specificity of AtClpS1, 60,61 a high‐resolution structure of AtClpS in the presence of bound peptide was needed. Initially, we tried to determine AtClpS1 in complex with an N‐degron using the LC3B fusion technique by attaching the Leu residue at the N‐terminal region of AtClpS1 for easier crystallization 62 .…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, ClpS1 in Arabidopsis thaliana (AtClpS1) showed a distinct N‐degron specificity that is linked to the translational capacity of plants 59 . It has been reported that AtClpS1 prefers the bulky aromatic residues Phe and Trp at the N‐terminus and shows weak binding to Leu and very weak or no binding to Ile and Tyr N‐termini 60 . This is not easy to explain because of the high‐sequence homology between bacterial and plant ClpS 47,60 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This results in the accumulation of Ac-HspQ in the cell, which binds to ClpS and inhibits the turnover of N-degron substrates by ClpAP 70 . Remarkably, in Arabidopsis thaliana another YccV-like protein, termed ClpF is also believed to modulate the activity of ClpS 72 , a putative plastid-localised N-recognin, for delivery of N-degron bearing substrates to the AAA+ protease, ClpCP 73 , 74 . Hence, it appears that YccV-like proteins not only regulate proteolytic pathways and/or machines in bacteria and the plastids of plants but also in human mitochondria as revealed by our data.…”
Section: Discussionmentioning
confidence: 99%
“…Amino‐terminal proteomic analysis of the chloroplast stroma indicated that peptides with specific residues at the N‐terminus were underrepresented (Rowland et al ), and reporter proteins in transplastomic plants showed differential stabilities dependent on their Nt‐residues (Apel et al ), suggesting that N‐degron pathway(s) operate in the chloroplast. Recently ClpS1 specificity was investigated in vitro and recognition assays for GFP‐fusion proteins bearing defined Nt‐residues indicated a low specificity for bacterial N‐degrons, but high specificity recognition for Nt‐Phe or Nt‐Trp (Colombo et al ; Montandon et al ). These studies suggest a chloroplast N‐degron pathway with high specificity, though no substrates or transferase activities have yet been identified.…”
Section: Enzymatic Components Of Plant N‐degron Pathwaysmentioning
confidence: 99%